Overexpression of the Mas1 gene mitigated LPS-induced inflammatory injury in mammary epithelial cells by inhibiting the NF-κB/MAPKs signaling pathways - Yan, Shuping; Ju, Xianghong; Lao, Jianlong; Wen, Zhaohai; Yong, Yanhong; Li, Yin; Li, Youquan (Frontiers in Veterinary Science, 2024)
Breast infection is the primary etiology of mastitis in dairy cows, leading to a reduction in the quality of dairy products and resulting in substantial economic losses for animal husbandry. Although antibiotic treatment can eliminate the pathogenic microorganisms that induce mastitis, it cannot repair the inflammatory damage of mammary epithelial cells and blood milk barrier. Mas1 is a G proteincoupled receptor, and its role in lipopolysaccharide (LPS) -induced inflammatory injury to mammary epithelial cells has not been studied. LPS treatment of EpH4 EV cells led to a significant downregulation of Mas1 transcript levels, which attracted our great interest, suggesting that Mas1 may be an important target for the treatment of mastitis. Therefore, this study intends to verify the role of Mas1 in the inflammatory injury of EpH4 EV cells by gene overexpression technology and gene silencing technology. The findings demonstrated that the overexpression of the Mas1 gene effectively reversed the activation of the nuclear factor-κB/mitogen-activated protein kinase (NF-κB/MAPK) signaling pathways induced by LPS, while also suppressing the upregulation of pro-inflammatory mediators. Furthermore, overexpression of the Mas1 gene reversed the downregulation of zonula occludens 1 (ZO-1), Occludin, and Claudin-3 caused by LPS, suggesting that Mas1 could promote to repair the blood-milk barrier. However, the silencing of the Mas1 gene using siRNA resulted in a contrasting effect. These results indicated that Mas1 alleviated the inflammatory injury of mammary epithelial cells induced by LPS.